A Rare Case Report of Ileo-Ileal Intusucception In A Young Adult - Safia Rana; Bushra; Rubeena Mohroo; Monal Trisal; Alka Solanki; Sujata Jetley; Ajay Thakral (JK Science)
Intussusception is rarely found in adults, accounting for about 5% of all cases of intussusception. The lipomas found in ileum are usually asymptomatic, not needing any special intervention. Herein, we describe a case of 36-year-old female who presented with abdominal pain associated with projectile vomiting. Abdominal ultrasound sonography and computed tomography of abdomen were suggestive of intussusception. The patient underwent emergency laparotomy surgery and partial resection of the ileum, including the ileal mass, following reduction of the intussusception. The resected specimen was diagnosed on histopathology as an intestinal lipoma. The patient made a satisfactory recovery post operatively and was discharged.